Cleridae (Insecta: Coleoptera) type collection at National Forest Insect Collection (NFIC), Forest Research Institute, Dehradun (India) - Faisal, Mohammad; Singh, Sudhir; Yousuf, Mohammad (Zootaxa, 2014)
Clerids are small predacious beetles (Coleoptera) that belong to the family Cleridae. In the National Forest Insect Collection (NFIC) Cleridae is represented by 31 authentically identified specimens including types of 27 species. The type material of Cleridae, deposited in the NFIC, Forest Research Institute, Dehradun (India), is listed and illustrated with digital automontage photographs. A list of 27 type species of Cleridae, 13 holotypes and 14 paratypes with information on species names, reference of the original publication, all available information on labels of types (country, locality, date of collection, collector name, etc) along with colored photographs of types and the labels that are attached to them, taken with Auto-montage 3-D imaging system, is provided.